2022
DOI: 10.1007/s00018-022-04452-6
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific deletion of miR-181ab1 reduces liver tumour progression via upregulation of CBX7

Abstract: MiR-181 expression levels increased in hepatocellular carcinoma (HCC) compared to non-cancerous tissues. MiR-181 has been widely reported as a possible driver of tumourigenesis but also acts as a tumour suppressor. In addition, the miR-181 family regulates the development and function of immune and vascular cells, which play vital roles in the progression of tumours. More complicatedly, many genes have been identified as miR-181 targets to mediate the effects of miR-181. However, the role of miR-181 in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Cancer-suppressing miR-146a, which controls TLR and cytokine signaling, inhibits TRAF6 and IRAK1 genes [ 98 ]. Essential immune system regulators miR-150, miR-17/92 clusters, and miR-181 may have a role in cell survival and migration [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-suppressing miR-146a, which controls TLR and cytokine signaling, inhibits TRAF6 and IRAK1 genes [ 98 ]. Essential immune system regulators miR-150, miR-17/92 clusters, and miR-181 may have a role in cell survival and migration [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer, miR-181a has been found to play a central role in the malignant transformation of tumors. miR-181a promotes the development of hepatocellular carcinoma by regulating PTEN, CBX7, WIF1, and HOXB5 [ 38 , 39 , 40 , 41 ]. However, other reports have indicated that miR-181a is downregulated in HCC and plays a tumor suppressor role targeting cMet, Egr1, and TGF-β [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survival data and expression profiles of microRNAs and mRNAs in The Cancer Genome Atlas (TCGA) HCC dataset were downloaded and analyzed from the OncoLnc website ( http://www.oncolnc.org/ ) or cBioPortal according to the guidelines for citing or using TCGA ( https://www.cancer.gov/about-nci/organization/ccg/research/structural-genomics/tcga/using-tcga/citing-tcga ) ( 14 16 ). The TIMER2.0 ( http://timer.cistrome.org/ ) database was accessed to evaluate correlations between the abundance of immune cell infiltrates and VE-Cadherin expression ( 17 ).…”
Section: Methodsmentioning
confidence: 99%